Adherence to the Mediterranean Diet in Relation to Gastric Cancer in Afghanistan - Amiry, Freshta; Mousavi, Seyed Mohammad; Barekzai, Ahmad Mujtaba; Esmaillzadeh, Ahmad (Frontiers in Nutrition, 2022)
Background: Although adherence to the Mediterranean dietary pattern(MD) was associated with a reduced risk of several cancers, there is no report about diet-disease associations in Afghanistan, in particular about gastric cancer, which is highly prevalent. Objective: The aim of this study was to investigate the association between adherence to the Mediterranean diet in relation to gastric cancer in Afghanistan. Methods: This hospital-based case-control study was carried out on a total number of 270 subjects (90 cases and 180 controls) aged between 20-75 years. Using convenience-sampling method, cases and controls were selected. Cases were patients with gastric cancer whom condition was pathologically confirmed. Controls were apparently healthy people who were matched with cases in terms of age (±5 years) and sex. Assessment of dietary intakes was done using a pre-tested food frequency questionnaire, designed specifically for Afghanistan. Adherence to the Mediterranean dietary pattern was done based on the scores suggested in earlier studies. Results: Out of 270 studied subjects, 73% were males. We found that subjects in the highest tertile of MD score had 52% decreased odds of GC (OR: 0.48; 95% CI: 0.24-0.98, P-trend=0.05) compared with those in the lowest tertile. After adjustment for age and gender, individuals in the highest tertile of MD score had not a significant lower odds of gastric cancer (OR: 0.49; 95% CI: 0.24-1.01, P-trend=0.06). Further adjustment for other potential confounders did not affect the findings (OR: 0.43; 95% CI: 0.13-1.38, P-trend=0.41). Considering BMI in the last model, we found that participants with the highest MD score were 83% less likely to have gastric cancer than those in lowest tertile (OR: 0.17; 95% CI: 0.03-0.80, P-trend=0.14). Conclusion: We found that greater adherence to MD might be associated with a lower odds of gastric cancer.